2011
DOI: 10.1186/1471-2229-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wheat Bell1-type homeobox genes in floral organs of alloplasmic lines with Aegilops crassa cytoplasm

Abstract: BackgroundAlloplasmic wheat lines with Aegilops crassa cytoplasm often show homeotic conversion of stamens into pistils under long-day conditions. In the pistillody-exhibiting florets, an ectopic ovule is formed within the transformed stamens, and female sterility is also observed because of abnormal integument development.ResultsIn this study, four wheat Bell1-like homeobox (BLH) genes were isolated and named WBLH1 to WBLH4. WBLH1/WBLH3/WBLH4 expression was observed in the basal boundary region of the ovary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
(126 reference statements)
1
9
0
Order By: Relevance
“…These clones were sequenced and identified based on sequence similarity searches with BLASTN or BLASTX software at National Center for Biotechnology Information (NCBI) and The Institute for Genomic Research (TIGR) databases. The following proteins were identified: (1) WBLH1, a previously described wheat homeodomain protein (Mizumoto et al, 2011); (2) WVIP2 (Wilson et al, 2005), a protein sharing 93% amino acid similarity with the wild oat (Avena fatua) Viviparus1 Interacting Protein2 (VIP2; Jones et al, 2000); and (3) TdWNK5, a protein with 75% amino acid similarity to Arabidopsis With No Lys [K] 5 (AtWNK5), a member of the Arabidopsis WNK family of MAP kinases . Ubiquitination assay on TdRF1.…”
Section: Identification Of Tdrf1 Protein Interactorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These clones were sequenced and identified based on sequence similarity searches with BLASTN or BLASTX software at National Center for Biotechnology Information (NCBI) and The Institute for Genomic Research (TIGR) databases. The following proteins were identified: (1) WBLH1, a previously described wheat homeodomain protein (Mizumoto et al, 2011); (2) WVIP2 (Wilson et al, 2005), a protein sharing 93% amino acid similarity with the wild oat (Avena fatua) Viviparus1 Interacting Protein2 (VIP2; Jones et al, 2000); and (3) TdWNK5, a protein with 75% amino acid similarity to Arabidopsis With No Lys [K] 5 (AtWNK5), a member of the Arabidopsis WNK family of MAP kinases . Ubiquitination assay on TdRF1.…”
Section: Identification Of Tdrf1 Protein Interactorsmentioning
confidence: 99%
“…4), we demonstrated that the RING-finger protein TdRF1 interacts with WBLH1, TdWNK5, and WVIP2. The homotranscription factor WBLH1, previously isolated by Mizumoto et al (2011), is homologous to HvJuBEL1 (94% of amino acid similarity), which is involved in the control of leaf development (M眉 ller et al, 2001) and is part of the BEL1-like protein family whose members are involved in various developmental aspects (Mizumoto et al, 2011). TdWNK5 is 75% similar to AtWNK5, a member of the Arabidopsis WNK family of MAP kinases .…”
Section: A Small Stress-related Interactome Around Tdrf1mentioning
confidence: 99%
See 1 more Smart Citation
“…BLH form heterodimeric complexes with STM and BP. This KNOX-BLH interaction is conserved among various plant species (Mizumoto et al, 2011;Arnaud and Pautot, 2014;Sharma et al, 2014).…”
Section: Class 1 Knox Homeodomain Transcription Factorsmentioning
confidence: 99%
“…TdRF1 guides to degradation the transcription factor WBLH1 whose barley homolog HvJuBEL1 controls leaf development. 5,6 TdRF1 is phosphorylated by TdWNK5 which belongs to the WNK family of kinases known to have a role in the control of flowering time. 7 For WVIP2 an interaction with the master regulator of embryo dormancy VP1 can be hypothesized based on its extensive homology with the Avena fatua Af VIP2.…”
mentioning
confidence: 99%